2022
DOI: 10.1007/s40263-022-00927-z
|View full text |Cite
|
Sign up to set email alerts
|

The Two Sides of Siponimod: Evidence for Brain and Immune Mechanisms in Multiple Sclerosis

Abstract: Siponimod is a selective sphingosine 1-phosphate receptor subtype 1 (S1P 1 ) and 5 (S1P 5 ) modulator approved in the United States and the European Union as an oral treatment for adults with relapsing forms of multiple sclerosis (RMS), including active secondary progressive multiple sclerosis (SPMS). Preclinical and clinical studies provide support for a dual mechanism of action of siponimod, targeting peripherally mediated inflammation and exerting direct central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…The immunomodulatory properties of siponimod impair the autoreactive lymphocytes egress from the lymph nodes and thus prevent their infiltration into the CNS and reduce inflammation 22 . In addition, siponimod could cross the blood–brain barrier (BBB) and exhibit neuroprotective effects in various preclinical models by directly interacting with the CNS‐resident cells 23–25 . We recently showed that siponimod treatment exerted neuroprotection against glaucoma injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunomodulatory properties of siponimod impair the autoreactive lymphocytes egress from the lymph nodes and thus prevent their infiltration into the CNS and reduce inflammation 22 . In addition, siponimod could cross the blood–brain barrier (BBB) and exhibit neuroprotective effects in various preclinical models by directly interacting with the CNS‐resident cells 23–25 . We recently showed that siponimod treatment exerted neuroprotection against glaucoma injury.…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, siponimod could cross the blood-brain barrier (BBB) and exhibit neuroprotective effects in various preclinical models by directly interacting with the CNS-resident cells. [23][24][25] We recently showed that siponimod treatment exerted neuroprotection against glaucoma injury. Further, the study revealed that neuronal S1PR1 ablation enhanced neuronal degeneration and siponimod mediates its protective effects through neuronal S1PR1 in experimental glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, apart from diffusion, active mechanisms such as receptor-mediated transport exist for drug uptake into the CNS [79]. Siponimod targets both S1P1 and S 1 P 5 receptors on BBB endothelial cells [80], which might contribute to an active transport into the brain. Inhibition of S1P1 receptors, specifically in endothelial cells, results in a transient opening of the BBB [81].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, activation of LPA 2 in situ in the heart by using appropriate methods such as gene therapy or specific agonist, combined with an appropriate delivery modality, might provide other options to reduce the pro-tumorigenic concerns. S1P 1 , which is also a lysophospholipid receptor and highly homologous to the LPA receptor family, has been shown to maintain endothelial function and vascular patency, and with the use of the S1P1 agonist FTY720, no obvious adverse events were found in small-scale human trials, 54 and is a proven drug target through S1P receptor modulators that now include 4 FDA-approved medicines, 55,56 supporting the possibility of cardiac therapeutics targeting LPA 2 .…”
Section: Pei Etmentioning
confidence: 99%